E-payment at the local government level: a study of Majlis Bandaraya Shah Alam and Majlis Daerah Kampar - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza; Zamin, Nurhawani; Mohd. Noor, Norzailawati (Malaysian Institute of Planners, 2014)
Information and Communication Technology (ICT) adoption through the implementation of electronic government (e-Government) helps improves local authority‘s service delivery for the benefit of the community. Many of the local authorities have adopted the online payment method for the assessment rate collection. Despite the notion that e-Government increased productivity and improved efficiency, citizen‘s usage is still considered minimal and has been comparatively low especially in services involving transactional. This study investigates the factors influencing the usage of online payment method in local authority‘s assessment rate collection. Data for this study was collected through questionnaire, interview and document analysis. The findings showed that perceived usefulness, perceived ease of use, perceived risk, payment receipt issuance and income level seem to influence user‘s intention to adopt the online payment method.